Home Office Saves a Tenth of Fuel - Oskar Jost; Holger Seibert (Wirtschaftsdienst)
Abstract In light of the sharp rise in fuel prices, this article takes up an important discussion on potential fuel savings. We argue that the work from home capacity, which developed during the COVID-19 pandemic, could be used to reduce commuting and thus fuel consumption. In order to determine the amount of fuel savings, we use a study available for Germany that provides information on work from home capacities for different occupations. Further, we merge this information with the employment statistics of the Federal Employment Agency providing information on occupations and commuting. This approach enables us to identify employees working and living in different municipalities, which are particularly affected by sharp rises in fuel prices.